RELATIONSHIP BETWEEN SOIL ACIDITY AND PRODUCTIVITY OF BANANA (Musa spp.) IN URABÁ, COLOMBIA - Delgado Bejarano, Laura; Calle , Diego Alexander; Cardona , Sindy Paola; Castañeda Sánchez, Darío; Bernal , Miguel Ángel; Zapata Henao, Sebastián (Chilean Journal of Agricultural & Animal Sciences, 2023)
Soil acidity plays an important role in the productivity of export bananas as it affects nutrient availability and phytotoxicity depending on soil pH. The objective of this research was to evaluate the relationship between soil pH and banana productivity in Uraba, Colombia. The study was conducted at the Ramiro Jaramillo Sossa experimental station, Banana Research Center (Cenibanano), Urabá, Antioquia. The sampling grid consisted of 110 points. Determination of pH was conducted in situ, and soil samples were processed in the laboratory using two solutions: distilled water and KCl. Significant differences were found between the solutions, aluminum extraction and field sampling. Additionally, the presence of Al3+ was confirmed in the pH range H2 O ? 5.5. Finally, the pH values were pH KCl < pH H2 O < pH in-situ. The latter best explained the behavior of bunch weight, indicating that in situ determination of pH better reflects the real conditions of this variable, with a greater relationship with productivity.